mTORC1 inhibition impairs activation of the unfolded protein response and induces cell death during ER stress in cardiomyocytes - Sandmann, Christoph; Löwenthal, Zoe; Aghajani, Marjan; Kaufman, Randal J.; Katus, Hugo; Frey, Norbert; Glembotski, Christopher C.; Völkers, Mirko; Doroudgar, Shirin (American journal of physiology. Heart and circulatory physiology, 2023)
The mechanistic target of rapamycin complex 1 (mTORC1) is a central regulator of protein synthesis that senses and responds to a variety of stimuli to coordinate cellular metabolism with environmental conditions. To ensure that protein synthesis is inhibited during unfavorable conditions, translation is directly coupled to the sensing of cellular protein homeostasis. Thus, translation is attenuated during endoplasmic reticulum (ER) stress by direct inhibition of the mTORC1 pathway. However, residual mTORC1 activity is maintained during prolonged ER stress, which is thought to be involved in translational reprogramming and adaption to ER stress. By analyzing the dynamics of mTORC1 regulation during ER stress, we unexpectedly found that mTORC1 is transiently activated in cardiomyocytes within minutes at the onset of ER stress before being inhibited during chronic ER stress. This dynamic regulation of mTORC1 appears to be mediated, at least in part, by ATF6, as its activation was sufficient to induce the biphasic control of mTORC1. We further showed that protein synthesis remains dependent on mTORC1 throughout the ER stress response and that mTORC1 activity is essential for posttranscriptional induction of several unfolded protein response genes. Pharmacological inhibition of mTORC1 increased cell death during ER stress, indicating that the mTORC1 pathway serves adaptive functions during ER stress in cardiomyocytes potentially by controlling the expression of protective unfolded protein response genes. - - NEW & NOTEWORTHY Cells coordinate translation rates with protein quality control to ensure that protein synthesis is initiated primarily when proper protein folding can be achieved. Long-term activity of the unfolded protein response is therefore associated with an inhibition of mTORC1, a central regulator of protein synthesis. Here, we found that mTORC1 is transiently activated early in response to ER stress before it is inhibited. Importantly, partial mTORC1 activity remained essential for the upregulation of adaptive unfolded protein response genes and cell survival in response to ER stress. Our data reveal a complex regulation of mTORC1 during ER stress and its involvement in the adaptive unfolded protein response.
Online veröffentlicht: 9. Juni 2023
Gesehen am 06.10.2023